Hinter-den-Kulissen von Planet der Affen Spezial-Dokumentation - Burns, Kevin; Comtois, David; Geryak, Cory; MacDowall, Roddy (Planet der Affen, 2001)
This documentary was originally made for television as part of a 30th anniversary celebration of one of the most beloved science fiction movie series in history. Most "making-ofs" are usually limited to an hour (or half that) in length to squeeze in the essentials but never go fully in-depth. "Behind the Planet of the Apes" is an exception to that rule. While many science-fiction films to come out of the '50s and '60s deserved to be sent to academic review boards, the original "Planet of the Apes" was one of the few to score straight "A's". This documentary, hosted by the late Roddy McDowall, takes us through the genesis of that original classic, the phenomenon it became and the desperation of studio executives to keep it alive. [apolloguide.com]